Beyond Maternal Sensitivity: Predictive Model of Attachment Quality; [Más Allá de la Sensibilidad Materna: Modelo Predictivo de la Calidad del Apego] - Guajardo-Sainz, H; Lecannelier-Acevedo, F (Pontificia Universidad Catolica de Chile, 2024)
Studies about attachment between babies and mothers have been the object of medical and social sciences, from genetic to cultural studies. As part of the huge diversity of research on this topic, the predictive explanation of how and if maternal behaviors could explain the quality and styles of attachment in infants, has been a current problematic question of study. This study analyzes if a specific model of maternal behaviors could predict the quality and style of attachment during early infancy, controlling maternal and infant mental health, through a micro-analytic observational methodology. Hundred three dyads were assessed using the experimental procedures of strange situation and AMBIANCE. Multinomial regressions models were used to test the statistic model proposed. The results indicate that maternal behavior related to communication errors could predict both the quality and type of attachment of the infant, controlling the mental health of the mother and child since in 71.5% of cases, communication errors would explain the variance of developed infant attachment (Nagelkerke s r2 = 0.715); p < 0.001). This model may be a promising avenue for developing preventive programs in children s mental health. The present study is the first carried out in Latin-America under this type of microanalytical methodology. © 2023 by Psykhe